Coding all-in-one for dummies - Minnick, Chris (For dummies, 2022)
The go-to guide for learning coding from the ground-up Adding some coding know-how to your skills can help launch a new career or bolster an old one. Coding All-in-One For Dummies offers an ideal starting place for learning the languages that make technology go. This edition gets you started with a helpful explanation of how coding works and how it's applied in the real-world before setting you on a path toward writing code for web building, mobile application development, and data analysis. Add coding to your skillset for your existing career, or begin the exciting transition into life as a professional developer—Dummies makes it easy. * Learn coding basics and how to apply them * Analyze data and automate routine tasks on the job * Get the foundation you need to launch a career as a coder * Add HTML, JavaScript, and Python know-how to your resume This book serves up insight on the basics of coding, designed to be easy to follow, even if you've never written a line of code in your life. You can do this.